Hemodynamic stability during labor and delivery with continuous epidural infusion - Gerhardt, Mark A; Gunka, Vit B; Miller, Robert J (The Journal of the American Osteopathic Association, 2006)
Epidural anesthesia for labor pain is frequently complicated by maternal hypotension. To test whether continuous epidural infusion (CEI) of local anesthetic, without bolus administration, lowers the incidence of hypotension in parturient patients. In a single-blind clinical study, subjects were randomly assigned to CEI-only (10 mL/h of 0.2% ropivacaine hydrochloride without bolus) or control (10 mL of 0.2% ropivacaine hydrochloride per hour with 10-mL bolus) epidural dosing groups. The incidence of hypotension (20% decrease in systolic blood pressure or mean arterial pressure (MAP), systolic blood pressure lower than 100 mm Hg, or MAP lower than 65 mm Hg) was recorded for 2 hours after dosing. Statistical analysis included a 2x2 chi(2) analysis, the Fisher exact test, and paired two-tailed t tests. Fifty subjects were studied, with 25 randomly assigned to each study group (CEI-only vs control). Baseline blood pressure was not different between groups (CEI-only, 127 [11]/77 [8.7] mm Hg; control, 131 [14]/78 [2]). The incidence of hypotension was lower in the CEI-only group than in the control group (5 [20%] vs 15 [60%]; P=.009), with intervention required in 1 (20%) of 5 CEI-only subjects and 7 (47%) of 15 control subjects. Sensory block reached the T10 dermatome in 54.4 (18) minutes in the CEI-only group and 38 (24) minutes in the control group (P=.04). Pain scores and maternal and fetal pulse rates were not different between groups. Analgesic supplementation (250 microg of epidural fentanyl) was used more frequently in the CEI-only group (72% vs 32%; P=.01), without adverse effects. Continuous epidural infusion of 0.2% ropivacaine hydrochloride without bolus administration reduces the incidence of hypotension by 67% and is safer than traditional bolus dosing for routine labor. This method requires further study in high-risk patients, including those with preeclampsia and cardiovascular disease.